Collembola Density and Diversity along a Gradient of Land- Use Types in Embu District, Eastern Kenya - Muturi, John J.; Mbugi, J.P.; Mueke, J.M.; Lagerlóf, Jan; Mungatu, J.K.; Nyamasyo, G.; Gikungu, M. (My University, 2009)
Populations of soil-dwelling Collembola were monitored on a land use gradient ranging from Natural forests to intensively cultivated land during the wet season October-November, 2007 and dry season February-March, 2008. Eight land use types (LUTs) which included stands of; Eucalyptus saligna, Vitex keniensis, Pennisetum purpureum, indigenous forest, fallow fields, Cammelia sinensis, Coffea africana and Zea mays intercropped with Phaseolus vulgaris were sampled for Collembola in Embu district. Collembola population densities of (15,111 M²) were collected in the study area. The Collembolan populations were lower in all sites during the dry season (5,445 M²), compared to those of wet season (9,666 M²). However, the highest Collembolan population was observed in undisturbed indigenous forest (38,089 M²) during the dry season. A total of seventeen genera in seven families were recorded. The genus Isotomiella was the most abundant followed by Cryptopygus, Folsomina and Parisotoma respectively. Results from this study revealed that abundance, diversity and species richness decreased along land use gradient with agro-based LUTs presenting an impoverished community. The level of organic matter as indicated by proportion of Carbon and Nitrogen in LUTs such as Indigenous forest, Eucalyptus forest and Cammelia sinensis seemed to influence highly Collembolan assemblages. The study concludes that land use intensification (land disturbance) negatively influences the abundance and species richness of soil Collembolan communities.
Keywords: Mesofauna; land intensification; Collembola and land use types